Fluorescent Carbon Dots from Nerium oleander: Effects of Physical Conditions and the Extract Types - Simsek, Sinem; Alas, Melis Ozge; Ozbek, Belma; Genc, Rukan (SPRINGER/PLENUM PUBLISHERS, 2019)
In this original research, the synthesis of carbon nanodots (CDs) from two different solvent extracts of Nerium oleander by the thermal method was investigated under various physical conditions such as pH, reaction temperature, ionic strength, and surface passivation agent (polyethylene glycol, PEG) presence in the reaction media. The effects of extract types and physical conditions on CDs formation were characterized by UV-Visible spectrophotometry, fluorescence spectrophotometry, Fourier transform infrared spectroscopy and dynamic light scattering analysis. Fluorescent CDs were obtained from PEG included reaction media. Additionally, the enhanced fluorescence intensity correlated with ascending reaction temperature was reported. The hydrodynamic particle size of CDs in aqueous solution was determined between similar to 1 and 235 nm with negative surface potential in the range of -6 mV and -28 mV. Moreover, CDs synthesized from aqueous extract mostly resulted in smaller size than that of ethanol extract based ones. The impact of surface passivation with PEG on the fluorescence feature of CDs was verified. For the relevant extracts of Oleander, CDs synthesized from PEG included formulations at pH 5 and NaCl free reaction media found as better alternatives than CDs synthesized under other conditions taking account their effect on fluorescence feature, hydrodynamic size and etc.
Keywords: Carbon nanodot; Nerium oleander; Fluorescent nanoparticles; Green synthesis; Thermal synthesis; MICROWAVE-ASSISTED SYNTHESIS; QUANTUM DOTS; NANODOTS SYNTHESIS; NANOPARTICLES; FACILE; LUMINESCENT; LEAVES; PHOTOLUMINESCENCE; CYTOTOXICITY; Biochemistry & Molecular Biology; Chemistry